Strategi Digitalisasi Rekrutmen Pegawai di Charitas Hospital Kenten Melalui Pengembangan Aplikasi - Ramadhan, Dimaz Gymnastiar; Hermaya, Nickholas Hansel; Yulistia, Yulistia (Universitas Multi Data Palembang, 2025)
One of the tools for submitting applications that is often used by companies is through email in the recruitment or selection process of employees. This causes difficulties for the HR department in managing digital files that often need to be reprinted for evaluation purposes. Therefore, it is necessary to develop a web-based recruitment and selection application for Charitas Hospital Kenten to improve the efficiency and effectiveness of the recruitment process. The application development method used is the Waterfall method, which includes the stages of software requirements analysis, design, implementation, and testing. The result of this research is an information system that assists in managing digital documents and enhances the efficiency of the recruitment process at Charitas Hospital Kenten .